Kuda Laut sebagai Inspirasi Motif Sablon DTF (Direct Transfer Film) pada Evening Gown - Aisyah Angela; Indarti Indarti (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
Sea horse is an animal in the Hippocampus species in the form of a jagged body shape with a head resembling a horse, a crown on the head and a pointed elongated tail in accordance with a unique morphological shape and looks strange. The purpose of this study is to describe the process of making motif designs and the resulting motifs on evening dresses using DTF screen printing with seahorse inspiration. This research method uses the Double Diamond Model which consists of 4 stages, namely Discover, Define, Develop, and Deliver. In the early stages of determining the direction of the evening dress design by exploring the source of seahorse ideas to be used as a moodboard. The second stage is to develop the moodboard into fashion design sketches and motifs. The third stage is making 10 fashion design developments by placing motifs. The fourth stage is testing the feasibility of the clothing by selecting 1 best design to be realized into a product by making a production design, making a prototype on the total and testing the DTF screen printing. The results of this study resulted in a DTF screen printing motif inspired by a seahorse and transformed into an evening dress with an I silhouette, applying decorations and using colors that match the inspiration.